Analysis of the Effect of Investment, Agglomeration, and Human Development Index on Regional Inequality in Eastern Indonesia 2019-2023 - Aditya, Dhea Nerizza; Suparta, I Wayan; Taher, Arivina Ratih Yulihar (CV. ITTC INDONESIA, 2025)
This study aims to analyze the effect of Domestic Investment (PMDN), economic agglomeration, and Human Development Index (HDI) on regional inequality in 12 eastern Indonesian provinces during the 2019-2023 period. Regional inequality is measured using the Williamson Index, which reflects the level of economic inequality between regions. The analysis method used is panel data regression with the Fixed Effect Model (FEM) approach. The results show that FDI and agglomeration have a positive and significant influence on regional inequality, meaning that increased investment and concentration of economic activity can actually widen the gap if not balanced with equalization policies. Meanwhile, HDI has a negative and significant effect, indicating that improving people's quality of life can reduce regional inequality. The model has a coefficient of determination of 94.29%, which indicates that the three independent variables make a large contribution in explaining the variation in inter-regional inequality. These findings provide an important basis for the government to formulate more inclusive and equitable development policies in eastern Indonesi